Being young and resilient in times of AI, disasters, and crises - Veselin Mitrović (Stanovništvo)
Disasters, crises, and resilience are interconnected with a general comprehension of “normality” or everyday routine disrupted by sudden and adverse events. However, some inconsistencies in the above interpretation induce an epistemological and existential crisis. First, the everyday life of some disadvantaged groups can be described as catastrophic and miserable whether the general community recognizes it or not. Nevertheless, some of the usually resilient groups could become future icons of the new risk, particularly AI hazards. Second, disasters are, by definition, sudden events with identified timeframes, while crises can be long-lasting with the tendency to become omnipresent. Third, when compared with earlier assertions, particular groups may undergo a long-lasting and gradual crisis that diminishes their capacity to anticipate future events, a critical aspect of resilience, and influences the social structure. An exemplary case is the unregulated widespread use of artificial intelligence (AI) by students to complete tasks, which diminishes critical thinking and reduces significant cognitive engagement. Such actions are possible with the cultural complicity of various stakeholders. Ultimately, the dystopian vision of a mindless and non-resilient young populace within an already susceptible context of an aging society—particularly with the increasing prevalence of dementia—reveals novel vulnerabilities, signalling the onset of an impending disaster. The suggestion made in this paper is for the research and teaching community to play a more active role in mitigating, if not preventing, potential unintended yet not-so-unforeseeable consequences.